1993
DOI: 10.1288/00005537-199312000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Supracricoid hemilaryngopharyngectomy in selected pyriform sinus carcinoma staged as T2

Abstract: From 1964 to 1985 supracricoid hemilaryngopharyngectomy (SCHLP) was performed at the authors' institution for 34 selected pyriform sinus carcinomas staged as T2. Tumors involved the anterior part of the pyriform sinus, the lateral wall, the medial wall, and the whole aryepiglottic fold in all cases. Tumors with invasion of the apex of the pyriform sinus, of the retrocricoid region, of the posterior pharyngeal wall, or with fixation of the true vocal cord were excluded from the study. Such a technique was aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 17 publications
3
43
0
3
Order By: Relevance
“…Our low local recurrence rate has also been noted by other authors like Laccourreye et al, [6][7] Ogura et al, 8 Vandenbrouck. 1 Our distant metastatic rate of 15% was high and similar to that noted by El Badawi et al 9 in a series of 71 hypopharyngeal tumors staged T1 or T2.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our low local recurrence rate has also been noted by other authors like Laccourreye et al, [6][7] Ogura et al, 8 Vandenbrouck. 1 Our distant metastatic rate of 15% was high and similar to that noted by El Badawi et al 9 in a series of 71 hypopharyngeal tumors staged T1 or T2.…”
Section: Discussionsupporting
confidence: 89%
“…Pneumonia from aspiration was noted in 4% of cases in our series. When the ipsilateral vocal cord is resected, pneumonia from aspiration occurs more frequently; Laccourreye et al 6 reported a higher rate after supracricoid hemilaryngopharyngectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Vandenbrouck et al 28 reported local control in 16 (89%) of 18 patients (UICC T1, 17 patients; T2, 1 patient) treated with conservation surgery at the Institut Gustave-Roussy. Laccourreye et al 30 reported on a series of 34 selected patients with T2 pyriform sinus carcinoma who underwent a supracricoid hemilaryngopharyngectomy at the Hôpital Laennec; patients had follow-up for Ն6 years. One patient had a local recurrence develop; the 5-year local control rate was 97%.…”
Section: Proportion Of Patients Suitable For Conserva-mentioning
confidence: 99%
“…Vandenbrouck et al 28 observed that 2 of 18 patients undergoing a conservative operation required permanent tracheostomies. Laccourreye et al 30 observed no fatal postoperative complications in 34 patients treated with conservation surgery alone or combined with adjuvant RT or chemotherapy. Completion laryngectomy was performed in 2 patients (6%) because of persistent aspiration, and 1 patient died of chondronecrosis.…”
mentioning
confidence: 98%
See 1 more Smart Citation